Comparative characterization of key odorants of French fries and oils at the break-in, optimum, and degrading frying stages - Xu, Lirong; Mei, Xue; Chang, Jiarui; Wu, Gangcheng; Zhang, Hui; Jin, Qingzhe; Wang, Xingguo (Food chemistry, 2022)
•Three stages of flavor development in French fries (FFs): break-in, optimum, and degrading.•Key aroma compounds of FFs and SO were clarified by molecular sensory science.•Oxidation at TPC above 22.70% in frying oil induced rancid off-flavor. Flavor is a significant factor determining the popularity of French fries (FFs). The frying process of soybean oil (SO) showed three obvious stages—break-in, optimum, and degrading. Further, in order to distinguish the key aroma compounds in each stage, the FFs prepared in SO with total polar compounds (TPC) of 6.5% (FF7), 16.37% (FF16), and 26.5% (FF27), and their corresponding oils (SO7, SO16, SO27) were chosen for sensory-directed analysis. In the break-in stage (6.50–13.50% of TPC), the flavor of the FFs was light and undesirable due to the lower content of (E,E)-2,4-decadienal. Then at the optimum stage (15.43–22.70% of TPC), the FFs obtained a higher sensory score, mainly owing to the increase of (E,E)-2,4-decadienal with a strong, deep-fried odor. However, in the degrading stage (over 22.70% of TPC), high level of four acids (hexanoic, heptanoic, octanoic, and nonanoic acid), benzeneacetaldehyde and trans-4,5-epoxy-(E)-2-decenal resulted in flavor deterioration in FF27.